2018
DOI: 10.1364/optica.5.000450
|View full text |Cite
|
Sign up to set email alerts
|

Dose efficient Compton X-ray microscopy

Abstract: X-ray imaging techniques have proven invaluable to study biological systems at high resolution due to the penetration power and short wavelength of this radiation. In practice, the resolution and sensitivity of current X-ray imaging techniques are not limited by the performance of optics or image-recovery methods but by radiation damage. We propose the use of Compton (inelastic) X-ray scattering for high-resolution cellular imaging and provide a study of a scanning microscope geometry that requires a dose to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 44 publications
(64 reference statements)
3
31
1
Order By: Relevance
“…In addition, the Howells et al (2009) model of the dose threshold as a function of resolution is shown together with a more recent one (Atakisi et al, 2019) obtained from radiation-damage studies of protein crystals. Similar diagrams occur in the works by Shen et al (2004), Howells et al (2009) andVillanueva-Perez et al (2018). The Atakisi radiation-damage model assumes that local disordering reactions occur.…”
Section: Most Of the Examples Insupporting
confidence: 52%
See 4 more Smart Citations
“…In addition, the Howells et al (2009) model of the dose threshold as a function of resolution is shown together with a more recent one (Atakisi et al, 2019) obtained from radiation-damage studies of protein crystals. Similar diagrams occur in the works by Shen et al (2004), Howells et al (2009) andVillanueva-Perez et al (2018). The Atakisi radiation-damage model assumes that local disordering reactions occur.…”
Section: Most Of the Examples Insupporting
confidence: 52%
“…Within the water window, a significant amount of dose could be deposited within the feature for large highly absorbing organelles such as lipid droplets. In addition, the Compton cross section and resultant deposition of energy in the sample have to be included as discussed in the work by Villanueva-Perez et al (2018). This latter term is excluded from the calculations in this article as, at the X-ray energies considered, dose is mainly dependent on photoelectric absorption.…”
Section: Fluence and Dosementioning
confidence: 99%
See 3 more Smart Citations